Manajemen Keuangan Perusahaan Syariah: (Studi Kasus Pada Keuangan Dana Tabarru Asuransi Takaful Keluarga Tahun 2020-2021) - Adrian Adrian; Asmuni Asmuni; Hasman Zhafiri Muhammad; Tommy Pratama; Syahmirwan Syahmirwan (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
This study aims to examine more deeply the material related to corporate financial management, which in this study will focus more on family takaful insurance companies, this research method is through a literature study by collecting literature related to looking at all sources related to the financial performance of tabarru funds. by using a literature study, then every data found by the author will try to separate between what is considered true and not true. The results of this study indicate that tabarru funds are used by family takaful insurance companies to help fellow customers in need, then takaful applies the principle of shring of risk realized through the collection of tabarru funds, so as to be able to create solidarity, mutually protect relationships and establish kinship among participants. Then the participant's funds are managed by family takaful insurance based on a tijarah contract which is free from elements of obscurity, usury gambling etc., participant funds will be invested in sharia-based investment instruments such as sharia stocks, sukuk, syr'i mutual funds, so that they can move the economy to realize people's welfare